Effectiveness of Allergic Rhinitis Management Related to WHO Guideline on Allergic Rhinitis and Its Impact on Asthma (ARIA) - Atika Aziza; Arif Dermawan; Vycke Yunivita Kusumah Dewi (Althea Medical Journal, 2016)
Background: The standard procedure of Allergic Rhinitis (AR) Management in Indonesia is based on Allergic Rhinitis and Its Impact on Asthma (ARIA) World Health Organization (WHO) 2008 guideline; however, it needs some adjustment to get an effective use locally in Indonesia. The data related to the problem however did not exist in Indonesia. The study aimed to evaluate the effectiveness of AR patient management based on the ARIA WHO guideline in the Department of Otorhinolaryngology-Head and Neck Surgery Dr. Hasan Sadikin General Hospital Bandung.Methods: The study was conducted from September to October 2015 using quantitative descriptive design to observe the development of ARIA classification, total nasal symptom score (TNSS), and quality of life (QoL) during the first 6 months of therapy. The data were obtained from medical records of AR patients who visited the Rhinology-Allergy clinic Department of Otorhinolaryngology-Head and Neck Surgery Dr. Hasan Sadikin General Hospital within one year. Thirty three patients were included in the study using total sampling.Results: There was significant improvement (p<0.001) in ARIA classification, TNSS, and QoL between the initiation of therapy, the third, and the sixth month. In contrary, there was no significant difference in ARIA classification (p=0.109), TNSS (p=0.317), and QoL (p=1.000) between the third and the sixth month of therapy.Conclusions: Allergic rhinitis patient management based on the 2008 ARIA WHO guideline is effective. [AMJ.2016;3(4):538–44]Keywords: Allergic rhinitis, asthma, effectiveness, management DOI: 10.15850/amj.v3n4.651